Medication-induced inhibition of the activity of sensing quorum of Pseudomonas aeruginosa bacteria - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2019)
The scientific review deals with the modern concepts of the quorum sensing systems LasI/R, RhlI/R, PqsABCDH/R and IQS of Pseudomonas aeruginosa bacteria, the functioning of which causes their survival under the most unfavorable and bactericidal conditions. For writing the article, information was searched using Scopus, Web of Science, MedLine, PubMed, Google Scholar, EMBASE, Global Health, The Cochrane Library, CyberLeninka, RISC. High antibiotic resistance of Pseudomonas aeruginosa bacteria as causative agents for nosocomial infectious diseases is due to the ability to create a biofilm. The mechanisms of biofilm formation by Pseudomonas aeruginosa bacteria, which are represented by the quorum sensing system LasI/R, RhlI/R, PqsABCDH/R and IQS, are described. The data of scientific studies that reveal the role of quorum sensing-dependent virulence factors of the bacteria Pseudomonas aeruginosa in the pathogenesis of the infectious process are presented. The hierarchical unified organization of the quorum sensing of Pseudomonas aeruginosa bacteria in the formation of a biofilm was demonstrated. The formation of biofilm by Pseudomonas aeruginosa bacteria predetermines the lack of effectiveness of antibiotic therapy and the risk of developing a chronic process. Attention is focused on the possibilities of drug suppression of quorum sensing-associated factors of bacterial virulence and biofilm formation when using any molecular component of the quorum system of sensing bacteria Pseudomonas aeruginosa as a target. The characteristics of some compounds that inhibit the sensory system of Pseudomonas aeruginosa bacteria are given, and it is likely that they will be able to develop medicines for use in medical practice for the treatment of infections caused by Pseudomonas aeruginosa bacteria.